Checklist of library building design considerations - Sannwald, William W. (Chicago American Library Association, 2009)
Guides librarians and other members of a building design team through the stages of the design process. The checklist format provides a clear, concise way of itemizing the issues, helping your construction project run as smoothly as possible!
Building planning and architecture -- Library site selection -- Sustainable design -- General exterior considerations -- Interior organization of library buildings -- Compliance with ADA accessibility guidelines -- Telecommunications, electrical, and miscellaneous equipment -- Interior design and finishes -- Materials handling and storage : book stacks and shelving -- Building systems -- Safety and security -- Maintenance of library buildings and property -- Building occupancy and post-occupancy evaluation -- Groundbreaking and dedication ceremonies.
Electronic reproduction.
Keywords: Library architecture -- United States; Electronic books